Biological aspects: Summary and consensus statements of group 2. The 5th EAO Consensus Conference 2018. (10th October 2018) - Sanz, Mariano; Klinge, Bjorn; Alcoforado, Gil; Bienz, Stefan P.; Cosyn, Jan; De Bruyn, Hugo; Derks, Jan; Figuero, Elena; Gurzawska, Katarzyna; Heitz‐Mayfield, Lisa; Jung, Ronald E.; Ornekol, Turker; et al.
Abstract: Objectives: This publication reports the EAO Workshop group‐2 discussions and consensus statements which provided the scientific evidence on the influence of biological parameters on implant‐related clinical outcomes. Material and methods: The first publication was a systematic review on the biological effects of abutment material on the stability of peri‐implant marginal bone levels and the second, a critical narrative review on how peri‐implant diagnostic parameters correspond with long‐term implant survival and success. The group evaluated the content of both publications, made corrections and recommendations to the authors and agreed on the consensus statements, clinical recommendations and recommendations for future research, which are described in this consensus report. Results: Tested abutment materials can be considered appropriate for clinical use according to the observation period studied (mean 3.5 years). Mean peri‐implant bone loss and mean probing pocket depths are not adequate outcomes to study the prevalence of peri‐implantitis, while the reporting of frequency distributions is considered more appropriate. Conclusions: Titanium is currently considered the standard of care as abutment material, although other materials may be more suitable for aesthetic locations. Peri‐implantitis should be diagnosed through composite evaluations of peri‐implant tissue inflammation and assessment of marginal bone loss with different thresholds.